Intravenous n-3 fatty acids in the critically ill. Issue 2 (March 2019) - Mayer, Konstantin; Schaefer, Martina B.; Hecker, Matthias
Abstract : Purpose of review: Lipid emulsions are an integral part of parenteral nutrition. Enteral nutrition is the preferred route to feed critically ill patients and parenteral nutrition is used in case of contraindications or when enteral nutrition does not reach the nutritional goals. n-3 Lipids are included into some newer lipid emulsions including fish oil or may be added by a fish oil-based lipid emulsion to lipid emulsion without fish oil. This review focuses on recent clinical trials, metaanalyses, and guidelines of parenteral nutrition with n-3 lipids in critically ill patients. Recent findings: Two single-center studies report a mortality benefit of adding fish oil-based lipid emulsions to the parenteral nutrition. Metaanalyses performed without these two studies had demonstrated beneficial effects of n-3 lipids regarding infections, length of stay, and time of mechanical ventilation but not on mortality. However, all metaanalyses judged the database derived from the underlying studies as not sufficient for a firm recommendation. Consecutively, guidelines and expert groups issue very cautious recommendations for the use of n-3 lipids in parenteral nutrition. Summary: Beneficial effects of n-3 lipids in trials and metaanalyses became available; however, high-quality multicenter randomized controlled trials are needed before more endorsing recommendation will be available.